1999
DOI: 10.1177/103841629900800108
|View full text |Cite
|
Sign up to set email alerts
|

Career Aspirations of Young Aboriginal Women

Abstract: This article focuses on the career aspirations of young female Aboriginal students at high school. Its aim is to contribute to a greater understanding of these clients' needs and concerns in order to be able to not only assist them with appropriate information and contacts but to help develop an awareness of relevant issues for careers advisers. It is the thesis of this article that careers advisers who liaise with both education and vocational institutions are well placed to facilitate the career decision-mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A number of studies have drawn attention to the influence of family and community in relation to the aspirations of Indigenous students (Craven et al, 2005;Gool & Patton, 1999;Parkes, McRae-Williams, & Tedmanson, 2015). However, the importance of recognising heterogeneity within Indigeneity has also been emphasised.…”
Section: Prior Studies On the Aspirations Of Australian Indigenous School Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have drawn attention to the influence of family and community in relation to the aspirations of Indigenous students (Craven et al, 2005;Gool & Patton, 1999;Parkes, McRae-Williams, & Tedmanson, 2015). However, the importance of recognising heterogeneity within Indigeneity has also been emphasised.…”
Section: Prior Studies On the Aspirations Of Australian Indigenous School Studentsmentioning
confidence: 99%
“…While there is a small body of research that specifically addresses the aspirations of Indigenous students, it mostly focuses on the secondary school level (Craven et al, 2005;Gool & Patton, 1999;Hossain, Gorman, Williams-Mozely, & Garvey, 2008;Senior & Chenhall, 2012;Sikora & Biddle, 2015). Moreover, although outreach initiatives between universities and schools (Bennett et al, 2015;Kinnane, Wilks, Wilson, Hughes, & Thomas, 2014;Shah & Widin, 2010) and mentoring programs such as the Australian Indigenous Mentoring Experience (Harwood, McMahon, O'Shea, Bodkin-Andrews, & Priestly, 2015;O'Shea, Harwood, Kervin, & Humphry, 2013) are critical mechanisms to inform and solidify aspirations as well as facilitate access to higher education for Indigenous students, a recent review of such initiatives found that these are often focused on students at the later stages of schooling (Bennett et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This favouring of mothers as role models, consistent with other studies, may be due to the important role mothers have in the lives of their children as carers and supporters (Bricheno & Thornton, 2007). Additionally, women's relatives are recognised amongst Indigenous people as being the “backbone of the family” and necessary figures for girls who require “strong female role models” (Sophia & Patton, 1999). Furthermore, Mothers and women family members generally portray traditional feminine characteristics (i.e., nurturing, caring and giving), which girls tend to be socialised to be drawn to admire and adopt (Biskup & Pfister, 1999; Drury et al., 2011; Sophia & Patton, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, women's relatives are recognised amongst Indigenous people as being the “backbone of the family” and necessary figures for girls who require “strong female role models” (Sophia & Patton, 1999). Furthermore, Mothers and women family members generally portray traditional feminine characteristics (i.e., nurturing, caring and giving), which girls tend to be socialised to be drawn to admire and adopt (Biskup & Pfister, 1999; Drury et al., 2011; Sophia & Patton, 1999).…”
Section: Discussionmentioning
confidence: 99%